Knowledge discovery for knowledge based systems : some experimental results - Rancan, Claudio Jorge; Kogan, Ariel; Pesado, Patricia Mabel; García-Martínez, Ramón (2007)
This paper addresses some considerations based on the state of the involved technologies for the integration of knowledge discovery systems and knowledge based systems centered in automatic knowledge acquisition for experts systems. Some experimental results related to the quality of the generated knowledge bases are shown.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Research in Computing Science, 27, pp. 3-13
Keywords: SISTEMAS BASADOS EN CONOCIMIENTO